Seasonal variation in the growth of Gracilaria edulis (Gmelin) Silva cultured from spores - Jayasankar, Reeta; Ramamoorthy, N (Indian Journal of Fisheries, 2011)
An year-round experiment was conducted in the culture of Gracilaria edulisby reproductive method in the Gulf of Mannar and Palk Bay, near Mandapam,along the southeast coast of India. The spores liberated on cement blocks weretransplanted to Palk Bay in April after 17 days of spore output and nurseryrearing. The germlings were transferred to the Gulf of Mannar during Augustwhen the size of the plants ranged between 0.3 and 1.9 cm (mean 0.88 cm)with a crop growth rate of 0.011 cm/day. The CGR was more pronounced fromOctober being 0.043 cm/day and increased gradually till harvest reaching apeak value of 0.650 cm/day during March. The harvested plants were young,healthy and sterile. October to March was found to be the most suitable periodfor cultivation.